Low prevalence of atrial fibrillation in ischaemic stroke: Underestimating a modifiable risk factor - Mayet, Mohammed (Afr J Emerg Med, 2021)
INTRODUCTION: Cerebrovascular disease remains one of the leading causes of morbidity and mortality globally. In South Africa, it was the fourth leading cause of death in 2016, responsible for 5.1% of all deaths - the leading cause of death in individuals 65 years and older. Atrial fibrillation accounts for 15% of all strokes and 25% are diagnosed when patients present with a stroke. We set out to determine the prevalence of atrial fibrillation in patients with confirmed ischaemic strokes in a district level hospital in the Western Cape, South Africa. METHODS: This descriptive study was conducted at Mitchells Plain Hospital in Cape Town and data was collected over a one-year period. Patients diagnosed with a stroke were identified from an electronic patient register and relevant radiology and clinical data were sourced retrospectively. The diagnosis of ischaemic stroke was confirmed by a CT scan report and ECGs were independently screened by two Emergency Physicians. Ethical approval was granted by the University of Cape Town Human Research Ethics Committee [790/2018]. RESULTS: The proportion of adult patients with a stroke diagnosis was 2%. Of the included cases, 80% had ischaemic strokes and 11% had haemorrhagic strokes. 11% of all patients with ischaemic strokes had atrial fibrillation, 67% of those presumed new. A total of 60 (15%) of all patients with ischaemic stroke were aged 45 years or younger. The inpatient mortality rate was statistically higher in patients who had atrial fibrillation (26% vs 7%, p < 0.001). CONCLUSION: With the increasing population life expectancy, and prevalence of cardiovascular disease the prevalence of atrial fibrillation and its complications will increase. Since the risk of stroke related to atrial fibrillation can be reduced significantly by oral anticoagulation, further studies should aim to explore barriers and challenges to effective screening.